Sosialisasi Bencana Tanah Longsor dan Kebakaran di MI Al- Huda 01 Pandanarum - Indyah Hartami Santi; Ardi Eka Putra; Maysa Aulia Salsabila; Muhammad Devana Putra Faizin Pratama; Reinhard Forno; Venny Eka Kurniawati (Yayasan Daarul Huda Kruengmane, 2023)
Sociabilization is a term that generally refers to the process of learning to interact with other individuals through understanding thoughts, feelings, and actions that are important for effective participation in social life. This sociabilization process is something that constantly occurs in our daily lives. One of the government programs related to this is the Disaster Reduction Program, which is aimed at providing education to the community. The aim of this research is to enhance children's understanding of recognizing disasters. The research problem is divided into three stages in the communication process, namely preparation, create ppt, and implementation. In the implementation of this community service program, the method used encompasses two aspects, namely sociabilization and simulation. Sociabilization is one form of communication, and thus, it is a communication process in itself. Meanwhile, simulation is used to apply this method and appears to have been carried out in various groups. However, the actual field experience is only experienced by a small portion of students, so the simulation may not accurately reflect real-life situations. Based on the results of this sociabilization, it is evident that providing education on disaster mitigation to students in Madrasah Ibtidaiyah is crucial for enhancing their knowledge. Considering that the topic of disasters may be new to students, they have a high interest in understanding and studying it thoroughly.